Pengembangan E-Book Interaktif DARBUKA Bermuatan Alat Musik Madura untuk Siswa Kelas V SDN Telang 1 - Rika Nur Hamida; Fachrur Rozie (Mataram University, 2026)
Learning in the Merdeka Curriculum encourages the use of digital and contextual teaching materials that actively engage students. However, science learning on sound for fifth-grade students at SDN Telang 1 still relied on printed textbooks and teacher-centered instruction, making it difficult for students to understand abstract concepts while local cultural content was rarely integrated into learning. This study aims to develop the DARBUKA Interactive E-book incorporating Madurese musical instruments for fifth-grade students of SDN Telang 1 that is valid, effective, and attractive. This research employed the Research and Development (R&D) method using the 4D model, consisting of the Define, Design, Development, and Disseminate stages. The results showed that the DARBUKA Interactive E-book achieved a very high level of validity, with learning design validation of 95%, material validation of 91.67%, and teaching material validation of 83.75%. In terms of effectiveness, the e-book achieved 100% student learning mastery in both the limited trial and implementation stages, supported by teacher and student activities categorized as very good. Teacher responses reached 97.5% (very attractive), while student responses were categorized as attractive. Therefore, the DARBUKA Interactive E-book is feasible as a teaching material because it is valid, effective, and attractive, while supporting active, interactive, meaningful, and culturally contextual learning for elementary school students.